Study of GLUT-4 and AMPK gene expression and phosphorylation of AMPK protein in Oyster Mushroom induced Type 2 diabetic model rats - Asrafuzzaman, Md. (BRAC University, 2018)
This thesis report is submitted in Partial Fulfillment of the Requirements’ for the Degree of Master of Science in Biotechnology 2017.